Agonistic autoantibodies against ß2-adrenergic receptor influence retinal microcirculation in glaucoma suspects and patients - Hohberger, Bettina; Hosari, Sami; Wallukat, Gerd; Kunze, Rudolf; Krebs, Johann Ferdinand; Müller, Magdalena; Hennig, Till; Lämmer, Robert; Horn, Folkert; Garcia Munoz, Luis Enrique; Herrmann, Martin; Mardin, Christian (PLoS ONE, 2021)
PURPOSE: Agonistic β2-adrenergic receptor autoantibodies (β2-agAAb) have been observed in sera of patients with ocular hypertension and open-angle glaucoma (OAG). They target the β2-receptors on trabecular meshwork, ciliary body and pericytes (Junemann et al. 2018; Hohberger et al. 2019). In addition to their influence on the intraocular pressure, an association to retinal microcirculation is discussed. This study aimed to investigate foveal avascular zone (FAZ) characteristics by en face OCT angiography (OCT-A) in glaucoma suspects and its relationship to β2-agAAb status in patients with OAG. MATERIAL AND METHODS: Thirty-four patients (28 OAG, 6 glaucoma suspects) underwent standardized, clinical examination including sensory testing as white-on-white perimetry (Octopus G1, mean defect, MD) and structural measures as retinal nerve fibre layer (RNFL) thickness, neuroretinal rim width (BMO-MRW), retinal ganglion cell layer (RGCL) thickness, and inner nuclear layer (INL) thickness with high-resolution OCT. FAZ characteristics were measured by OCT-A scans of superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). FAZ-R was calculated (area FAZ (SVP)/area FAZ (ICP)). Using cardiomyocyte bioassays we analysed serum samples for the presence of β2-agAAb. RESULTS: (I) Total mean FAZ area [mm2]: 0.34±0.16 (SVP), 0.24±0.12 (ICP), and 0.49±0.24 (DCP); mean FAZ-R 1.58±0.94. No correlation was seen for FAZ-R with MD, RNFL, BMO-MRW, RGCL thickness and INL thickness (p>0.05). (II) ß2-agAAb have been observed in 91% patients and showed no correlation with MD, RNFL, BMO-MRW, RGCL thickness and INL thickness (p>0.05). (III) FAZ-R correlated significantly with the β2-agAAb-induced increase of the beat rate of cardiomyocyte (p = 0.028). CONCLUSION: FAZ characteristics did not correlate with any glaucoma associated functional and morphometric follow-up parameter in the present cohort. However, level of β2-agAAb showed a significantly correlation with FAZ-ratio. We conclude that β2-agAAb might be a novel biomarker in glaucoma pathogenesis showing association to FAZ-ratio with OCT-A.
CRIS-Team Scopus Importer:2021-05-21

Agonistic beta 2-adrenergic receptor autoantibodies characterize the aqueous humor of patients with primary and secondary open-angle glaucoma - Hohberger, Bettina; Woern, Max; Lämmer, Robert; Herrmann, Martin; Mardin, Christian; Kruse, Friedrich; Kunze, Rudolf; Wallukat, Gerd (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Agonistic beta 2-Adrenergic Receptor Autoantibodies Characterize the Aqueous Humor of Patients With Primary and Secondary Open-Angle Glaucoma - Hohberger, Bettina; Worn, Max; Lämmer, Robert; Mahajan, Aparna; Mardin, Christian; Schlötzer-Schrehardt, Ursula; Kunze, Rudolph; Herrmann, Martin; Wallukat, Gerd (Frontiers in Immunology, 2021)
Purpose
CRIS-Team WoS Importer:2021-05-28

Agonistic beta 2-Adrenergic Receptor Autoantibodies: Longitudinal analysis of the efficacy of beta-adrenoceptor antagonist on intraocular pressure - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Lämmer, Robert (2018)
EVALuna2:34742

A Keypoint Detection and Description Network Based on the Vessel Structure for Multi-modal Retinal Image Registration - Sindel, Aline; Hohberger, Bettina; Fassihi Dehcordi, Sebastian; Mardin, Christian Y.; Lämmer, Robert; Maier, Andreas; Christlein, Vincent (Bildverarbeitung für die Medizin 2022, 2022)
Ophthalmological imaging utilizes different imaging systems, such as color fundus, infrared, fluorescein angiography, optical coherence tomography (OCT) or OCT angiography. Multiple images with different modalities or acquisition times are often analyzed for the diagnosis of retinal diseases. Automatically aligning the vessel structures in the images by means of multi-modal registration can support the ophthalmologists in their work. Our method uses a convolutional neural network to extract features of the vessel structure in multi-modal retinal images. We jointly train a keypoint detection and description network on small patches using a classification and a cross-modal descriptor loss function and apply the network to the full image size in the test phase. Our method demonstrates the best registration performance on our and a public multi-modal dataset in comparison to competing method

Analysis of visual appearance of retinal nerve fibers in high resolution fundus images: a study on normal subjects - Kolar, Radim; Tornow, Ralf-Peter; Lämmer, Robert; Odstrcilik, Jan; Mayer, Markus Anton; Gazarek, Jiri; Jan, Jiri; Kubena, Tomas; Cernosek, Pavel (Computational and Mathematical Methods in Medicine, 2013)
The retinal ganglion axons are an important part of the visual system, which can be directly observed by fundus camera. The layer they form together inside the retina is the retinal nerve fiber layer (RNFL). This paper describes results of a texture RNFL analysis in color fundus photographs and compares these results with quantitative measurement of RNFL thickness obtained from optical coherence tomography on normal subjects. It is shown that local mean value, standard deviation, and Shannon entropy extracted from the green and blue channel of fundus images are correlated with corresponding RNFL thickness. The linear correlation coefficients achieved values 0.694, 0.547, and 0.512 for respective features measured on 439 retinal positions in the peripapillary area from 23 eyes of 15 different normal subjects.
EVALuna2:21171

Are agonistic beta 2-adrenergic receptor autoantibodies present in normal tension glaucoma and secondary open-angle glaucoma? - Hohberger, Bettina; Mardin, Christian Y.; Hosari, Sami; Lämmer, Robert; Kunze, Rudolf; Juenemann, Anselm; Schlötzer-Schrehardt, Ursula; Wallukat, Gerd; Herrmann, Martin (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Autoantibodies Activating the β2-Adrenergic Receptor Characterize Patients With Primary and Secondary Glaucoma - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Kara, Katja; Mardin, Christian Y.; Lämmer, Robert; Schlötzer-Schrehardt, Ursula; Hosari, Sami; Horn, Folkert; Munoz Becerra, Luis; Herrmann, Martin (Frontiers in Immunology, 2019)
Recently, agonistic autoantibodies (agAAb) activating the β2-adrenergic receptor were detected in primary open-angle glaucoma (POAG) or ocular hypertension (OHT) patients and were linked to intraocular pressure (IOP) (1). The aim of the present study was to quantify β2-agAAb in the sera of glaucoma suspects and patients with primary and secondary glaucoma. Patients with OHT (n = 33), pre-perimetric POAG (pre-POAG; n = 11), POAG (n = 28), and 11 secondary OAG (SOAG) underwent ophthalmological examinations including examinations with Octopus G1 perimetry and morphometry. Twenty-five healthy individuals served as controls. Serum-derived IgG samples were analyzed for β2-agAAb using a functional bioassay. The beat-rate-increase of spontaneously beating cultured neonatal rat cardiomyocytes was monitored with 1.6 beats/15 s as cut-off. None of the sera of normal subjects showed β2-agAAb. In POAG or OHT patients increased beating rates of 4.1 ± 2.2 beats/15 s, and 3.7 ± 2.8 beats/15 s were detected (p > 0.05). Glaucoma patients with (POAG) and without perimetric (pre-POAG) defects did not differ (pre-POAG 4.4 ± 2.6 beats/15 s, POAG 4.1 ± 2.0 beats/15 s, p > 0.05). Patients with SOAG yielded mean beating rates of 4.7 ± 1.7 beats/15 s (p > 0.05). β2-agAAb were seen in 73% of OHT, 82% of pre-POAG, 82% of POAG, and 91% SOAG patients (p < 0.001). Clinical data did not correlate with beating rate (p > 0.05). The robust β2-agAAb seropositivity in patients with OHT, pre-POAG, POAG, and SOAG suggest a primary common role for β2-agAAb starting early in glaucoma pathophysiology and turned out to be a novel marker identifying all patients with increased IOP independent of glaucoma stage and entity.
CRIS-Team Scopus Importer:2019-10-29
Keywords: autoantibodies; glaucoma; ocular hypertension; primary open-angle glaucoma; secondary open-angle glaucoma; β2-adrenergic receptor

Baseline magnetic resonance imaging of the optic nerve provides limited predictive information on short-term recovery after acute optic neuritis - Berg, Sebastian; Kaschka, Iris; Utz, Kathrin S.; Huhn, Konstantin; Laemmer, Alexandra; Lämmer, Robert; Waschbisch, Anne; Kloska, Stephan; Lee, De-Hyung; Dörfler, Arnd; Linker, Ralf (PLoS ONE, 2015)
In acute optic neuritis, magnetic resonance imaging (MRI) may help to confirm the diagnosis as well as to exclude alternative diagnoses. Yet, little is known on the value of optic nerve imaging for predicting clinical symptoms or therapeutic outcome.To evaluate the benefit of optic nerve MRI for predicting response to appropriate therapy and recovery of visual acuity.Clinical data as well as visual evoked potentials (VEP) and MRI results of 104 patients, who were treated at the Department of Neurology with clinically definite optic neuritis between December 2010 and September 2012 were retrospectively reviewed including a follow up within 14 days.Both length of the Gd enhancing lesion (r = -0.38; p = 0.001) and the T2 lesion (r = -0.25; p = 0.03) of the optic nerve in acute optic neuritis showed a medium correlation with visual acuity after treatment. Although visual acuity pre-treatment was little but nonsignificantly lower if Gd enhancement of the optic nerve was detected via orbital MRI, improvement of visual acuity after adequate therapy was significantly better (0.40 vs. 0.24; p = 0.04). Intraorbitally located Gd enhancing lesions were associated with worse visual improvement compared to canalicular, intracranial and chiasmal lesions (0.35 vs. 0.54; p = 0.02).Orbital MRI is a broadly available, valuable tool for predicting the improvement of visual function. While the accurate individual prediction of long-term outcomes after appropriate therapy still remains difficult, lesion length of Gd enhancement and T2 lesion contribute to its prediction and a better short-term visual outcome may be associated with detection and localization of Gd enhancement along the optic nerve.
EVALuna2:21236

Blue-Yellow VEP with Projector-Stimulation in Glaucoma - Dussan Molinos, Laura; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2021)
Background and aim In the past, increased latencies of the blue-on-yellow pattern visually evoked potentials (BY-VEP), which predominantly originate in the koniocellular pathway, have proven to be a sensitive biomarker for early glaucoma. However, a complex experimental setup based on an optical bench was necessary to obtain these measurements because computer screens lack sufficient temporal, spatial, spectral, and luminance resolution. Here, we evaluated the diagnostic value of a novel setup based on a commercially available video projector.
CRIS-Team WoS Importer:2021-12-03

Case Report: Neutralization of Autoantibodies Targeting G-Protein-Coupled Receptors Improves Capillary Impairment and Fatigue Symptoms After COVID-19 Infection - Hohberger, Bettina; Harrer, Thomas; Mardin, Christian; Kruse, Friedrich; Hoffmanns, Jakob; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; Szewczykowski, Charlotte; Schottenhamml, Julia; Kräter, Martin; Bergua, Antonio; et al. (Frontiers in Medicine, 2021)
Clinical features of Coronavirus disease 2019 (COVID-19) are caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Acute infection management is a substantial healthcare issue, and the development of long-Covid syndrome (LCS) is extremely challenging for patients and physicians. It is associated with a variety of characteristics as impaired capillary microcirculation, chronic fatigue syndrome (CFS), proinflammatory cytokines, and functional autoantibodies targeting G-protein-coupled receptors (GPCR-AAbs). Here, we present a case report of successful healing of LCS with BC 007 (Berlin Cures, Berlin, Germany), a DNA aptamer drug with a high affinity to GPCR-AAbs that neutralizes these AAbs. A patient with a documented history of glaucoma, recovered from mild COVID-19, but still suffered from CFS, loss of taste, and impaired capillary microcirculation in the macula and peripapillary region. He was positively tested for various targeting GPCR-AAbs. Within 48 h after a single BC 007 treatment, GPCR-AAbs were functionally inactivated and remained inactive during the observation period of 4 weeks. This observation was accompanied by constant improvement of the fatigue symptoms of the patient, taste, and retinal capillary microcirculation. Therefore, the removal of GPCR-AAb might ameliorate the characteristics of the LCD, such as capillary impairment, loss of taste, and CFS.
CRIS-Team Scopus Importer:2021-12-17
Keywords: BC 007; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; glaucoma; long-COVID syndrome; OCT angiography

Combined evaluation of frequency doubling technology perimetry and scanning laser ophthalmoscopy for glaucoma detection using automated classification - Horn, Folkert; Lämmer, Robert; Mardin, Christian Y.; Jünemann, Anselm; Michelson, Georg; Lausen, Berthold; Adler, Werner (Journal of Glaucoma, 2012)
To develop a diagnostic setup with classification rules for combined analysis of morphology [Heidelberg Retina Tomograph (HRT)] and function [frequency doubling technology (FDT) perimetry] measurements.We used 2 independent case-control studies from the Erlangen eye department as learning and test data for automated classification using random forests. One eye of 334 open angle glaucoma patients and 254 controls entered the study. All individuals underwent HRT scanning tomography of the optic disc, FDT screening, conventional perimetry, and evaluation of fundus photographs. Random forests were learned on individuals of the Erlangen glaucoma registry (102 preperimetric patients, 130 perimetric patients, 161 controls). The classification performances of random forests and built-in classifiers were examined by receiver operator characteristic analysis on an independent second cohort of individuals (47 preperimetric patients, 55 perimetric patients, 93 controls).HRT measurements had a higher diagnostic power for early glaucomas and FDT perimetry for glaucoma patients with visual field loss. A combination of all parameters using automated classification was superior to single tests in comparison to the diagnostic instrument with the higher diagnostic power in the respective group. Highest sensitivities at a fixed specificity (95%) in the patients of the present test population were: HRT=32%, FDT=19%, combined analysis=47% in preperimetric patients and HRT=76%, FDT=89%, combined analysis=96% in perimetric patients.The feasibility of machine learning for medical diagnostic assistance could be demonstrated in patients from 2 independent study populations. A predictive model using automated classification is able to combine the advantages of morphology and function, resulting in a higher diagnostic power for glaucoma detection.
EVALuna2:5313

Combining L- and M-cone-isolating stimuli to measure parvo- and magnocellular function in normal subjects and glaucoma patients - Huchzermeyer, Cord; Mardin, Christian Y.; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Comparison of Bruch's Membrane Opening Minimum Rim Width and Peripapillary Retinal Nerve Fiber Layer Thickness in Early Glaucoma Assessment - Gmeiner, Jonas M. D.; Schrems, Wolfgang; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Schrems-Hösl, Laura-Maria (Investigative Ophthalmology & Visual Science, 2016)
To compare the diagnostic value of Bruch's membrane opening minimum rim width (BMO-MRW) and retinal nerve fiber layer thickness (RNFLT) in patients with ocular hypertension, preperimetric, and perimetric glaucoma.One hundred eighty-one eyes consisting of 40 healthy controls, 41 ocular hypertensive subjects, 50 subjects with preperimetric glaucoma and 50 with perimetric glaucoma were included. One randomly selected eye was included. All patients underwent slit-lamp examination, funduscopy, achromatic perimetry, and 24-hour IOP profile. Bruch's membrane opening-MRW and RNFLT (3 peripapillary circle scans, 12°/14°/16°) data were obtained using spectral domain optical coherence tomography. Areas under the receiver operating characteristics curves (AUROC) as well as sensitivity at fixed specificity were computed globally and for six vertical split sectors. Venn diagrams were plotted to identify patients that were diagnosed by one of the two parameters only.For RNFLT the smallest circle diameter showed highest diagnostic accuracy and was used for comparison with BMO-MRW. Distinguishing perimetric glaucoma, RNFLT and BMO-MRW showed comparable AUROCs in global (AUROC, 95% confidence interval: 0.954, 0.911-0.996 and 0.929, 0.872-0.986) and sectoral (0.929, 0.877-0.981 and 0.946, 0.904-0.996) analysis. For preperimetric glaucoma BMO-MRW and RNFLT also demonstrated comparable performance in global (0.839, 0.757-0.921 and 0.821, 0.731-0.912) and sectoral (0.860, 0.782-0.938 and 0.835, 0.750-0.920) analysis. When identifying ocular hypertensive eyes AUROCs were lower for global RNFLT and BMO-MRW (0.493, 0.365-0.621 and 0.562, 0.433-0.691). A combined parameter showed an AUROC of 0.959, 0.921 to 0.996 for perimetric and 0.849, 0.770 to 0.929 for preperimetric glaucoma.Bruch's membrane opening-MRW and RNFLT are comparably useful parameters for discrimination of preperimetric and perimetric glaucomatous eyes and show potential to assist each other in glaucoma diagnosis. (www.ClinicalTrials.gov number, NTC00494923; Erlangen Glaucoma Registry.).
EVALuna2:21294

Comparison of frequency doubling and flicker defined form perimetry in early glaucoma - Horn, Folkert; Scharch, Vicki; Mardin, Christian Y.; Lämmer, Robert; Kremers, Jan (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To compare perimetric data based on the second-generation frequency doubling technology (FDT) and on flicker defined form (FDF) stimulation in early glaucoma patients.Seventy-two experienced glaucoma patients and 50 healthy subjects of the Erlangen Glaucoma Registry participated in the study. The definition of glaucoma was solely based on optic disc appearance. All patients underwent FDF perimetry (HEP), FDT perimetry (Matrix), standard automated perimetry (SAP, Octopus), and peripapillar measurements of the RNFL thickness (Spectralis OCT). Exclusion criteria were: mean defect (MD) in SAP > 6 dB, eye diseases other than glaucoma, or non-reliable FDF or FDT measurements. Statistical analyses included comparison of the standard indices and correlations between methods. Venn-diagrams show the number of patients with abnormal results in HEP, Matrix, SAP, and mean RNFL thickness.Mean defect data from FDT and FDF perimetry were strongly correlated (R = -0.85, P <0.001). In this cohort of early glaucoma patients, the MD values were 6.1 ± 5.0 dB (FDF) and 4.5 ± 4.1 dB (FDT). Sensitivity in this patient group was 65 % for FDF-MD, 60 % for FDT-MD, and 60 % for RNFL-thickness, all at a specificity of 95 %. The correlation analysis between local RNFL thickness and corresponding visual defects revealed significant Spearman correlation coefficients for the arcuate bundles of the visual field (FDF-inferior: R = -0.65, FDF-superior: R = -0.74, FDT-inferior: R = -0.55, FDT-superior: R = -0.72).FDF and FDT stimulations can be used to detect patients with early glaucoma. Combined consideration of RNFL thickness and results from one of these perimetric tests can increase the total number of detected patients.
EVALuna2:21278

Confocal Laser Scanning Tomography to Predict Visual Field Conversion in Patients With Ocular Hypertension and Early Glaucoma - Schrems-Hösl, Laura-Maria; Schrems, Wolfgang; Lämmer, Robert; Horn, Folkert; Jünemann, Anselm; Kruse, Friedrich; Mardin, Christian Y. (Journal of Glaucoma, 2016)
To compare Moorfields regression analysis (MRA), Glaucoma probability score (GPS), and different discriminant functions to predict future visual field conversion of patients with ocular hypertension and early glaucoma.The study included 120 eyes of patients with ocular hypertension and 110 eyes of patients with early glaucoma from the Erlangen glaucoma registry. Annually, all patients underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, and HRT (Heidelberg Retina Tomograph I-III; Heidelberg Engineering) measurements. The cohort was divided into 2 groups based on the development of repeatable glaucomatous visual fields. Positive predictive values and negative predictive values were compared for MRA, GPS, and the classification of Bathija, Iester, Mardin, and Mikelberg at baseline. Kaplan-Meier Survival curves and Logrank tests were used to evaluate equality of survival distributions for different test results.Median follow-up was 9.04 years. 26 eyes (11.3%) demonstrated glaucomatous visual field loss in the follow-up. MRA temporal-superior and temporal-inferior outside normal limits were predictive of future visual field loss with positive predictive values of 33.3% and 28.6%. Normal GPS Temporal Sector demonstrated a negative predictive value of 96.4% and normal results in discriminant functions between 94.7% and 95.5%.Confocal scanning laser tomography is a useful imaging modality to predict future visual field conversion. Development of visual field defects in 10 years is highly unlikely, if GPS classification and/or classification of discriminant analysis at baseline are normal. MRA temporal-superior and temporal-inferior outside normal limits are associated with future VF conversion (ClinicalTrials.gov number, NTC00494923).
EVALuna2:21172

Correlation between Loss of the Retinal Nerve Fiber Layer Thickness and Local Visual Field Defects measured with FDF-Perimetry - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 642 perimetry; 610 nerve fiber layer; 758 visual fields

Einfluss der Achsenlänge auf die 2-Jahres-Erfolgsrate der Stand-alone-und mit Phako/HKL kombinierten Xen45-Gel-Stentimplantation. - Gernhart, Markus; Hohberger, Bettina; Lämmer, Robert (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Up to now, no data have been available on the therapeutic success rate of Xen45 gel stent with respect to axial length (AL). The present study aimed to investigate a potential influence of AL on therapeutic success in stand-alone Xen45 gel stent implantation or combination with cataract surgery in open-angle glaucoma patients (OAG) with a follow-up of 2 years. Materials and Methods In this retrospective observational study, 98 eyes of 87 glaucoma patients of the Department of Ophthalmology, University of Erlangen Nürnberg, and from the Erlangen Glaucoma Registry (NCT00494923; ISSN 2191-5008, CS-2011) underwent stand-alone Xen45 gel stent implantation or a combination with cataract surgery. Therapeutic success was defined as ≥ 20% IOP reduction with the same or fewer anti-glaucomatous eye drops needed compared to baseline, yet without additional glaucoma-related surgery (expect bleb needling). Therapeutic failure was classified as any additional glaucoma-related surgery, IOP reduction < 20% or if more local anti-glaucomatous eye drops were applied compared to baseline. Results The therapeutic success rate was 60.7% (1 year) and 62.5% (2 years). No statistical difference was observed when procedures were combined with cataract surgery (p > 0.05). Subgroup analysis yielded no significantly different therapeutic success when considering glaucoma subtype [1 year: 61.5% (POAG), 60% (SAOG), 2 years: 54.5% (POAG), 69.2% (SOAG); p > 0.05]. Anti-glaucomatous medication use was lowered from 2.72 ± 1.04 at baseline to 0.61 ± 0.99 (1 year) and 0.7 ± 1.04 (2 years). The therapeutic success rate was seen to be independent of axial length for group and subgroup analysis (p > 0.05). Emmetropic eyes (22.0âŠ-âŠ24.5 mm) showed a statistically higher needling rate than myopic eyes (> 24.5 mm, p = 0.02). Conclusion Minimal invasive glaucoma surgery is one therapeutic option in OAG eyes, with good reduction in IOP even after 24 months (with additional bleb needling). Therapeutic success seemed to be independent of axial length in the present study.
CRIS-Team Scopus Importer:2021-04-02
Keywords: axial length; glaucoma; myopia; open-angle glaucoma; Xen Stent

Erlanger glaucoma registry: Effect of a long-term therapy with statins and acetyl salicylic acid on glaucoma conversion and progression - Thiermeier, Nina; Lämmer, Robert; Mardin, Christian Y.; Hohberger, Bettina (Biology, 2021)
Purpose: Drugs with cardiovascular protective properties (statins, acetylsalicylic acid (ASS)) were assumed to have positive effects on patients suffering from glaucoma disease. The present retrospective study aimed to investigate the influence of statins, ASS or a combination of both on the glaucoma conversion and progression rate in glaucoma suspects and glaucoma patients with a 20-year follow-up period. Methods: A retrospective analysis of 199 eyes of 120 patients (63 male, 57 female) of the Erlanger Glaucoma Registry (EGR; ClinicalTrials.gov Identifier: NCT00494923; ISSN 2191-5008, CS-2011) was performed considering systemic therapy with statins, ASS or a combination of both: 107 eyes with ocular hypertension (OHT) and 92 eyes with pre-perimetric primary open-angle glaucoma (pre-POAG). All patients received an ophthalmological examination including morphometric and functional glaucoma diagnostics. Glaucoma conversion was defined as the conversion of OHT to pre-POAG. Glaucoma progression was defined as confirmed visual field loss. Data were shown as percentages. Statistical analysis was performed by Chi-Quadrat tests. Results: 1. Glaucoma conversion/progression was observed in 46.7% of the subjects, additionally in combination with hypercholesterinemia in 76.8%. 2. Statins: 27.3% of eyes under systemic statin therapy showed a conversion/progression. Patients taking statins ≥ 10 years yielded a reduced conversion/progression rate (p = 0.028, non-significant after Bonferroni–Holm). 3. ASS: 34.7% of eyes under systemic ASS therapy showed a conversion/progression. A significantly lower con-version/progression rate was observed after ASS therapy ≥ 12 years (p = 0.017, significant after Bonferroni–Holm). 4. ASS and statins: 25.0% of eyes under combined therapy showed a conver-sion/progression. A significantly reduced conversion/progression rate was reached after 8 years of combined therapy (p = 0.049, non-significant after Bonferroni–Holm). Conclusions: Patients with ocular hypertension and early glaucoma seem to benefit from adjuvant cardiovascular protective therapy. However, the benefits and disadvantages of treatment with statins and/or ASS should be kept in mind. Thus, a thorough risk–benefit evaluation has to be performed for each patient individually to avoid unwanted side effects.
CRIS-Team Scopus Importer:2021-07-09
Keywords: ASS; Cholesterol; Glaucoma; Glaucoma suspect; Progression; Statins

Extended Ganglion Cell Layer Thickness Deviation Maps With OCT in Glaucoma Diagnosis - Lehmann, Paul; Hohberger, Bettina; Lämmer, Robert; Mardin, Christian (Frontiers in Medicine, 2021)
Purpose: The aim of the present study was to investigate the diagnostic power of RGCL in the macula quantitatively and qualitatively by using a conventional and extended elliptic grid with deviation maps. Subjects and Methods: Thickness of RGCL was measured using SPECTRALIS® OCT (Heidelberg Engineering, Heidelberg, Germany) in 150 eyes of 150 subjects of the Erlangen Glaucoma Registry (EGR; NTC00494923): 26 ocular hypertension (OHT), 39 pre-perimetric open-angle glaucoma (pre-OAG), 19 normal tension glaucoma (NTG), 34 primary open-angle glaucoma (POAG), 16 secondary open-angle glaucoma (SOAG), and 16 controls. Analysis of RGCL was done quantitatively (global value, GV) and qualitatively (qualitative total value, QTV) by using a color-coded point score for data of the common elliptic macular grid of deviation maps. Furthermore, qualitative analysis of RGCL was done for an extended elliptic macula grid (extended qualitative total value, eQTV). Receiver operating characteristic (ROC) curves were calculated for the conventional and the enlarged macular grid for all subjects' groups. Results: GV of RGCL thickness differed significantly between pre-OAG (p < 0.05), NTG (p < 0.001), POAG (p < 0.001), SOAG (p < 0.001), yet not OHT (p > 0.05) and controls, respectively. Quantitative ROC analysis of GV showed AUC of 0.965 (SOAG), 0.942 (POAG), 0.916 (NTG), 0.772 (pre-OAG), and 0.526 (OHT). QTV differed significantly between pre-POAG (p < 0.05), NTG (p < 0.001), POAG (p < 0.001), SOAG (p < 0.001), yet not OHT (p > 0.05) and controls, respectively. Qualitative ROC analysis of QTV showed AUCs of 0.908 (NTG) 0.914 (POAG), 0.930 (SOAG), 0.734 (pre-POAG), and 0.519 (OHT). Implementation of eQTV yielded even higher AUCs for NTG (0.919), POAG (0.969), and SOAG (0.973) compared to GV. Similar AUCs of eQTV and GV were observed for OHT (0.514) and pre-OAG (0.770). Conclusion: The results of the present study showed that quantitative and qualitative analysis of RGCL thickness yielded similar diagnostic impacts compared to RNFL. Qualitative analysis might be a quick and easy useable tool for clinical all-day life. The present data suggest that analysis of an extended macula region might improve its diagnostic impact.
CRIS-Team Scopus Importer:2021-06-25
Keywords: glaucoma; GRID; OCT; retinal ganlion cell; spectralis

Five-Year Long-Term Follow-Up of Selective Laser Trabeculoplasty in Open-Angle Glaucoma - Gack, Christina; Lämmer, Robert; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Selective laser trabeculoplasty (SLT) is known as a safe laser therapy for an effective reduction in intraocular pressure (IOP). The aim of this study was to examine the therapeutic success of SLT in open-angle glaucoma (OAG) patients with a long-term follow-up of 5 years. Methods Forty-six eyes of forty OAG patients, some with previous intraocular surgery, underwent SLT (24 males, 16 females). Therapeutic success was categorized as: category (I) - IOP reduction <= 21 mmHg and > 20% compared to baseline IOP with additional glaucoma medication; category (II) - IOP reduction <= 18 mmHg and > 30% compared to baseline IOP with additional glaucoma medication; category (III) - IOP reduction <= 18 mmHg without any additional glaucoma medication at all follow-ups. Therapeutic failure was defined as the necessity of any further glaucoma surgery (IV). Results (1) SLT was well tolerated in all eyes, and no severe side effects or complications were recorded. (2) After 1-year follow-up, therapeutic success was 27% (I), 30% (II), and 3% (III). The therapeutic failure rate was 40% (IV). (3) After 2 years follow-up, therapeutic success was 7% (I), 10% (II), and 0% (III). The therapeutic failure rate was 83% (IV). (4) After 3 years follow-up, the therapeutic failure rate increased up to 100% (IV). Conclusion SLT seemed to be effective in lowering IOP in the first year in the present cohort, however, the long-term effect is low and additional local therapy or surgical interventions are necessary.
CRIS-Team WoS Importer:2021-12-31

Glaucoma and Alzheimer: Neurodegenerative disorders show an adrenergic dysbalance - Hohberger, Bettina; Pruess, Harald; Mardin, Christian Y.; Lämmer, Robert; Mueller, Johannes; Wallukat, Gerd (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Glaucoma and Alzheimer: Neurodegenerative disorders show an adrenergic dysbalance - Hohberger, Bettina; Prüss, Harald; Mardin, Christian; Lämmer, Robert; Müller, Johannes; Wallukat, Gerd (PLoS ONE, 2022)
Glaucoma disease is characterized by an increased intraocular pressure (IOP), glaucomatous alterations of the optic disc and corresponding visual field defects. Even lowering the main risk factor IOP until an individual target level does not prevent this neurodegenerative disorder from proceeding. Several autoimmune mechanisms were discovered, partly showing a functionality. One of these autoimmune phenomena targets the ß2-adrenergic receptor (ß2-AR; i.e. agonistic autoantibodies; ß2-agAAb) and is linked to an elevated IOP and an impaired retinal microcirculation. As neurodegenerative disorder, Alzheimer's Disease (AD) is postulated to share a common molecular mechanism with glaucoma. In the present study we investigated autoimmune phenomena targeting the ß2-AR in patients with AD. Sera of the patients were analyzed in a rat cardiomyocyte bioassay for the presence of functional autoantibodies against ß2-AR. In addition, different species of amyloid beta (Aß) monomers were tested (Aß1-14, Aß10-25, Aβ10-37 Aß1-40, Aß1-42, Aβ28-40, and Aß-[Pyr]3-43). Our results demonstrate that none of the short-chain Aß (Aß1-14, Aß10-25, or Aβ28-40) showed any agonistic or inhibitory effect on ß2-AR. Contrary, long-chain Aß-[Pyr]3-43, representing a major neurogenic plaque component, exerted an activation that after blocking by the ß2-AR antagonist ICI118.551, could be identified as that the effect was realized via the ß2-AR. Moreover, the long chain Aß1-40, Aβ1-42, and Aβ10-37, yet not the short-chain Aß peptides prevented the clenbuterol induced desensitization of the ß2-AR. In addition, we identified functional autoantibodies in the sera of AD patients, activating the ß2-AR, like the ß2-agAAb found in patients with glaucoma. As autoimmune mechanisms were reportedly involved in the pathogenesis of glaucoma and Alzheimer's Disease, we postulate that overstimulation of the ß2-AR pathway can induce an adrenergic overdrive, that may play an important role in the multifactorial interplay of neurodegenerative disorders.
CRIS-Team Scopus Importer:2022-10-21

Glaucoma classification in 3 x 3 mm en face macular scans using deep learning in a different plexus - Schottenhamml, Julia; Wuerfl, Tobias; Mardin, Sophia; Ploner, Stefan; Husvogt, Lennart; Hohberger, Bettina; Lämmer, Robert; Mardin, Christian; Maier, Andreas (Biomedical Optics Express, 2021)
Glaucoma is among the leading causes of irreversible blindness worldwide. If diagnosed and treated early enough, the disease progression can be stopped or slowed down. Therefore, it would be very valuable to detect early stages of glaucoma, which are mostly asymptomatic, by broad screening. This study examines different computational features that can be automatically deduced from images and their performance on the classification task of differentiating glaucoma patients and healthy controls. Data used for this study are 3 x 3 mm en face optical coherence tomography angiography (OCTA) images of different retinal projections (of the whole retina, the superficial vascular plexus (SVP), the intermediate capillary plexus (ICP) and the deep capillary plexus (DCP)) centered around the fovea. Our results show quantitatively that the automatically extracted features from convolutional neural networks (CNNs) perform similarly well or better than handcrafted ones when used to distinguish glaucoma patients from healthy controls. On the whole retina projection and the SVP projection, CNNs outperform the handcrafted features presented in the literature. Area under receiver operating characteristics (AUROC) on the SVP projection is 0.967, which is comparable to the best reported values in the literature. This is achieved despite using the small 3 x 3 mm field of view, which has been reported as disadvantageous for handcrafted vessel density features in previous works. A detailed analysis of our CNN method, using attention maps, suggests that this pertbrmance increase can be partially explained by the CNN automatically relying more on areas of higher relevance for feature extraction. (C) 2021 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2021-12-17

Glaucoma detection using non-perfused areas in OCTA - Schottenhamml, Julia; Würfl, Tobias; Ploner, Stefan; Husvogt, Lennart; Lämmer, Robert; Hohberger, Bettina; Maier, Andreas; Mardin, Christian Y. (Scientific Reports, 2024)
Multiple ophthalmic diseases lead to decreased capillary perfusion that can be visualized using optical coherence tomography angiography images. To quantify the decrease in perfusion, past studies have often used the vessel density, which is the percentage of vessel pixels in the image. However, this method is often not sensitive enough to detect subtle changes in early pathology. More recent methods are based on quantifying non-perfused or intercapillary areas between the vessels. These methods rely upon the accuracy of vessel segmentation, which is a challenging task and therefore a limiting factor for reliability. Intercapillary areas computed from perfusion-distance measures are less sensitive to errors in the vessel segmentation since the distance to the next vessel is only slightly changing if gaps are present in the segmentation. We present a novel method for distinguishing between glaucoma patients and healthy controls based on features computed from the probability density function of these perfusion-distance areas. The proposed approach is evaluated on different capillary plexuses and outperforms previously proposed methods that use handcrafted features for classification. Moreover the results of the proposed method are in the same range as the ones of convolutional neural networks trained on the raw input images and is therefore a computationally efficient, simple to implement and explainable alternative to deep learning-based approaches.
CRIS-Team Scopus Importer:2024-05-10

Glaucoma Diagnostic Performance of GDxVCC and Spectralis OCT on Eyes With Atypical Retardation Pattern - Hoesl, Laura Maria; Tornow, Ralf-Peter; Schrems, Wolfgang; Horn, Folkert; Mardin, Christian Y.; Kruse, Friedrich; Jünemann, Anselm; Lämmer, Robert (Journal of Glaucoma, 2013)
: To investigate the impact of typical scan score (TSS) on discriminating glaucomatous and healthy eyes by scanning laser polarimetry and spectral domain optical coherence tomography (SD-OCT) in 32 peripapillary sectors.: One hundred two glaucoma patients and 32 healthy controls underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, GDxVCC, and SD-OCT measurements. For controls, only very typical scans (TSS=100) were accepted. Glaucoma patients were divided into 3 subgroups (very typical: TSS=100; typical: 99>=TSS>=80, atypical: TSS<80). Receiver operating characteristic curves were constructed for mean retinal nerve fiber layer values, sector data, and nerve fiber indicator (NFI). Sensitivity was estimated at >=90% specificity to compare the discriminating ability of each imaging modality.: For discrimination between healthy and glaucomatous eyes with very typical scans, the NFI and inferior sector analyses 26 to 27 demonstrated the highest sensitivity at >=90% specificity in GDxVCC and SD-OCT, respectively. For the typical and atypical groups, sensitivity at >>=90% specificity decreased for all 32 peripapillary sectors on an average by 10.9% and 17.9% for GDxVCC and by 4.9% and 0.8% for SD-OCT. For GDxVCC, diagnostic performance of peripapillary sectors decreased with lower TSS, especially in temporosuperior and inferotemporal sectors (sensitivity at >=90% specificity decreased by 55.3% and by 37.8% in the atypical group).: Diagnostic accuracy is comparable for SD-OCT and GDxVCC if typical scans (TSS=100) are investigated. Decreasing TSS is associated with a decrease in diagnostic accuracy for discriminating healthy and glaucomatous eyes by scanning laser polarimetry. NFI is less influenced than the global or sector retinal nerve fiber layer thickness. The TSS score should be included in the standard printout. Diagnostic accuracy of SD-OCT is barely influenced by low TSS.
EVALuna2:21037

Impact of acquisition area on deep-learning-based glaucoma detection in different plexuses in OCTA - Schottenhamml, Julia; Würfl, Tobias; Ploner, Stefan; Husvogt, Lennart; Lämmer, Robert; Hohberger, Bettina; Maier, Andreas; Mardin, Christian Y. (Scientific Reports, 2024)
Glaucoma is a group of neurodegenerative diseases that can lead to irreversible blindness. Yet, the progression can be slowed down if diagnosed and treated early enough. Optical coherence tomography angiography (OCTA) can non-invasively provide valuable information about the retinal microcirculation that has shown to be correlated with the onset of the disease. The vessel density (VD) is the most commonly used biomarker to quantify this vascular information. However, different studies showed that there is a great impact of the acquisition area on the performance of the VD to distinguish between glaucoma patients and a healthy control group. It also seems that the separate capillary plexuses are differently affected by the disease and therefore also influence the results. So in this study we investigate the impact of the acquisition area (3 × 3 mm macular scan, 6.44 × 6.4 mm macular scan, 6 × 6 mm optic nerve head (ONH) scan) and the different plexuses on the machine-learning-based distinction between glaucoma patients and healthy controls. The results yielded that the 6 × 6 mm ONH show the best performance over all plexuses. Moreover the deep learning-based approach outperforms the VD as a biomarker on every acquisition area and plexus. In addition to that, it also performs better than traditional biomarkers obtained from the OCT scans that are used in the clinical routine for diagnosis and progression tracking of glaucoma. Consequently, OCTA scans of the ONH might be a useful addition to OCT when studying glaucoma.
CRIS-Team Scopus Importer:2024-09-13

Influence of atypical retardation pattern on the peripapillary retinal nerve fibre distribution assessed by scanning laser polarimetry and optical coherence tomography - Schrems, Wolfgang; Lämmer, Robert; Hoesl, L. M.; Horn, Folkert; Mardin, C. Y.; Kruse, Friedrich; Tornow, Ralf-Peter (British Journal of Ophthalmology, 2011)
To investigate the influence of atypical retardation pattern (ARP) on the distribution of peripapillary retinal nerve fibre layer (RNFL) thickness measured with scanning laser polarimetry in healthy individuals and to compare these results with RNFL thickness from spectral domain optical coherence tomography (OCT) in the same subjects.120 healthy subjects were investigated in this study. All volunteers received detailed ophthalmological examination, GDx variable corneal compensation (VCC) and Spectralis-OCT. The subjects were divided into four subgroups according to their typical scan score (TSS): very typical with TSS=100, typical with 99 >= TSS >= 91, less typical with 90 >= TSS >= 81 and atypical with TSS <= 80. Deviations from very typical normal values were calculated for 32 sectors for each group.There was a systematic variation of the RNFL thickness deviation around the optic nerve head in the atypical group for the GDxVCC results. The highest percentage deviation of about 96% appeared temporal with decreasing deviation towards the superior and inferior sectors, and nasal sectors exhibited a deviation of 30%. Percentage deviations from very typical RNFL values decreased with increasing TSS. No systematic variation could be found if the RNFL thickness deviation between different TSS-groups was compared with the OCT results.The ARP has a major impact on the peripapillary RNFL distribution assessed by GDx VCC; thus, the TSS should be included in the standard printout.
EVALuna2:21007

Influence of Mitomycin C on the Therapeutic Success of Stand-Alone Xen45 Gel Stents and Its Combination with Cataract Surgery in Open-Angle Glaucoma Patients - Denkel, Laura; Hohberger, Bettina; Lämmer, Robert (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Minimally invasive glaucoma surgery (MIGS), like Xen45 gel stents, is known as effective therapy in lowering intraocular pressure (IOP); however, fibrotic reactions are a common problem in postoperative management. It was the aim of this study to investigate the therapeutic success of Xen45 gel stents as a stand-alone technique (Xen) and combined with cataract surgery (XenPhaco), and with antimetabolites (mitomycin C, MMC) in open-angle glaucoma patients. Methods Retrospective analysis was performed of 199 eyes of 177 glaucoma patients of the Department of Ophthalmology, University of Erlangen Nürnberg, and from the Erlangen Glaucoma Registry (NCT00494923; ISSN 2191-5008, CS-2011) who underwent implantation of a Xen45 gel stent. Therapeutic success was defined as IOP reduction of ≥ 20% on the same or less anti-glaucomatous medication after 12 months compared to preoperative and without any additional glaucoma-related surgery (except bleb needling). IOP reduction, reduction in local anti-glaucomatous eye drops, and intra- and postoperative complications were monitored. Results Stand-alone Xen45 gel stent: therapeutic success was reached in 39% (-MMC) and 55% (+MMC). Failure rate was 61% (-MMC) and 45% (+MMC). XenPhaco: therapeutic success was achieved in 57% (-MMC) and 46% (+MMC). Failure rate was 43% (-MMC) and 54% (+MMC). Data were not different for group and subgroup analyses (p > 0.05). Conclusions The use of MMC seemed to increase the therapeutic success rate after stand-alone Xen45 gel stent implantation and combined with cataract surgery, yet statistical significant was not reached.
CRIS-Team Scopus Importer:2021-06-04
Keywords: fibrosis; glaucoma; IOP; MIGS; MMC; Xen Stent

Inhibitory and Agonistic Autoantibodies Directed Against the β2-Adrenergic Receptor in Pseudoexfoliation Syndrome and Glaucoma - Hohberger, Bettina; Schlötzer-Schrehardt, Ursula; Mardin, Christian; Lämmer, Robert; Munoz, Luis Enrique; Kunze, Rudolf; Herrmann, Martin; Wallukat, Gerd (Frontiers in Neuroscience, 2021)
Pseudoexfoliation syndrome (PEXS) and glaucoma (PEXG) are assumed to be caused by a generalized elastosis leading to the accumulation of PEX material in ocular as well as in extraocular tissues. The exact pathophysiology of PEXS is still elusive. PEXG, the most common type of secondary open-angle glaucoma (OAG), is characterized by large peaks of intraocular pressure (IOP) with a progressive loss of the visual field. Agonistic autoantibodies (agAAbs) against the β2-adrenergic receptor (AR) have been shown to be present in sera of patients with primary and secondary OAG and ocular hypertension and are seemingly linked to IOP. In the present study, we investigated the autoantibodies directed against the β2-AR in sera of patients with PEXS and PEXG. We recruited 15, 10, and 15 patients with PEXG, PEXS, and primary OAG, respectively. Ten healthy individuals served as controls. All patients underwent standard ophthalmological examination with Octopus G1 perimetry. agAAbs prepared from serum samples were analyzed in a rat cardiomyocyte–based bioassay for the presence of agAAbs. We identified the interacting loop of the β2-AR and the immunoglobulin G (IgG) subclasses using synthetic peptides corresponding to the extracellular loops of the receptors and enzyme-linked immunosorbent assay, respectively. None of the controls were β2-agAAb–positive (0.2 ± 0.5 U). No β2-agAAbs (0.2 ± 0.4 U), but inhibitory β2-AAbs were observed in 80% of the patients that partially blocked the drug-induced β2-adrenergic stimulation; 5.8 ± 1.7 U vs. 11.1 ± 0.9 U for clenbuterol in the absence and the presence of sera from patients with PEXS, respectively. Epitope analyses identified the third extracellular loop of the β2-AR as the target of the inhibitory β2-AAbs, being of IgG3 subtype in PEXS patients. In contrast, patients with PEXG showed β2-agAAbs (5.6 ± 0.9 U), but no inhibitory ones. The β2-agAAbs levels of patients with PEXG and primary OAG patients (3.9 ± 2.8 U; p > 0.05) were at a similar level. In two cases of PEXG, the β2-agAAbs exert synergistic effects with clenbuterol. The activity increased from 11.5 ± 0.3 (clenbuterol only) to 16.3 ± 0.9 U. As autoimmune mechanisms were reportedly involved in the pathogenesis of glaucoma, agonistic and inhibitory β2-AAbs seem to be a part of this multifactorial interplay.
CRIS-Team Scopus Importer:2021-09-03
Keywords: autoantibodies; glaucoma; imbalanced autonomic theory; pseudoexfoliation; β

In Reply: Precision of Optic Nerve Head and Retinal Nerve Fiber Layer Parameter Measurements by Spectral-domain Optical Coherence Tomography, Methodological Issues on Reproducibility - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Lämmer, Robert; Kruse, Friedrich; Mardin, Christian Y. (Journal of Glaucoma, 2018)
Purpose:We report the occurrence of an extensive submacular hemorrhage after trabeculectomy with mitomycin C in a patient with an occult choroidal neovascular membrane (CNVM).Patients and Methods:A 66-year-old man had a 3-year history of primary open-angle glaucoma in the left eye, which had been treated with topical antiglaucoma medication. The patient had age-related macular degeneration with an occult CNVM, for which he had received 5 intravitreal injections of ranibizumab and 5 intravitreal injections of bevacizumab in the left eye over a 3-year period. As intraocular pressure was not under control in the left eye over a 2-month period, trabeculectomy with mitomycin C was performed.Results:On the first postoperative day, intraocular pressure was 8mmHg with a well-formed bleb in the left eye. However, extensive subretinal hemorrhage was observed, and the patient underwent pneumatic displacement and pars plana vitrectomy to remove the hemorrhage. After 7 months, extensive subretinal fibrosis was observed and visual acuity was low (hand movement only).Conclusions:To our knowledge, this is the first report of an extensive submacular hemorrhage after trabeculectomy with mitomycin C in a patient with an occult CNVM.
EVALuna2:34752

Intraocular pressure is influenced by ambient temperature in glaucoma patients - Krebs, Johann Ferdinand; Hosari, Sami; Lämmer, Robert; Mardin, Christian; Hohberger, Bettina (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Long COVID: Association of Functional Autoantibodies against G-Protein-Coupled Receptors with an Impaired Retinal Microcirculation - Szewczykowski, Charlotte; Mardin, Christian; Lucio, Marianna; Wallukat, Gerd; Hoffmanns, Jakob; Schröder, Tim; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; Beitlich, Lorenz; Schottenhamml, Julia; et al. (International Journal of Molecular Sciences, 2022)
Long COVID (LC) describes the clinical phenotype of symptoms after infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Diagnostic and therapeutic options are limited, as the pathomechanism of LC is elusive. As the number of acute SARS-CoV-2 infections was and is large, LC will be a challenge for the healthcare system. Previous studies revealed an impaired blood flow, the formation of microclots, and autoimmune mechanisms as potential factors in this complex interplay. Since functionally active autoantibodies against G-protein-coupled receptors (GPCR-AAbs) were observed in patients after SARS-CoV-2 infection, this study aimed to correlate the appearance of GPCR-AAbs with capillary microcirculation. The seropositivity of GPCR-AAbs was measured by an established cardiomyocyte bioassay in 42 patients with LC and 6 controls. Retinal microcirculation was measured by OCT–angiography and quantified as macula and peripapillary vessel density (VD) by the Erlangen-Angio Tool. A statistical analysis yielded impaired VD in patients with LC compared to the controls, which was accentuated in female persons. A significant decrease in macula and peripapillary VD for AAbs targeting adrenergic β2-receptor, MAS-receptor angiotensin-II-type-1 receptor, and adrenergic α1-receptor were observed. The present study might suggest that a seropositivity of GPCR-AAbs can be linked to an impaired retinal capillary microcirculation, potentially mirroring the systemic microcirculation with consecutive clinical symptoms.
CRIS-Team Scopus Importer:2022-07-15
Keywords: chronic fatigue syndrome; COVID-19; functionally GPCR autoantibodies; glaucoma; Long-COVID syndrome; OCT–angiography

Longitudinal analysis of progression in glaucoma using spectral-domain optical coherence tomography - Wessel, Julia M.; Horn, Folkert; Tornow, Ralf-Peter; Schmid, Matthias; Mardin, Christian Y.; Kruse, Friedrich; Jünemann, Anselm; Lämmer, Robert (Investigative Ophthalmology & Visual Science, 2013)
To compare the longitudinal loss of RNFL thickness measurements by SD-OCT in healthy individuals and glaucoma patients with or without progression concerning optic disc morphology.A total of 62 eyes, comprising 38 glaucomatous eyes with open angle glaucoma and 24 healthy controls, were included in the study (Erlangen Glaucoma Registry, NTC00494923). All patients were investigated annually over a period of 3 years by Spectralis SD-OCT measuring peripapillary RNFL thickness. By masked comparative analysis of photographs, the eyes were classified into nonprogressive and progressive glaucoma cases. Longitudinal loss of RNFL thickness was compared with morphological changes of optic disc morphology.Mixed model analysis of annual OCT scans revealed an estimated annual decrease of the RNFL thickness by 2.12 ?m in glaucoma eyes with progression, whereas glaucoma eyes without progression in optic disc morphology lost 1.18 ?m per year in RNFL thickness (P = 0.002). The rate of change in healthy eyes was 0.60 ?m and thereby also significantly lower than in glaucoma eyes with progression (P < 0.001). The intrasession variability of three successive measurements without head repositioning was 1.5 ± 0.7 ?m. The loss of mean RNFL thickness exceeded the intrasession variability in 60% of nonprogressive eyes, and in 85% of progressive eyes after 3 years.LONGITUDINAL MEASUREMENTS OF RNFL THICKNESS USING SD-OCT SHOW A MORE PRONOUNCED REDUCTION OF RNFL THICKNESS IN PATIENTS WITH PROGRESSION COMPARED WITH PATIENTS WITHOUT PROGRESSION IN GLAUCOMATOUS OPTIC DISC CHANGES. (www.clinicaltrials.gov number, NTC00494923.).
EVALuna2:5384

Longitudinal stability of the diurnal rhythm of intraocular pressure in subjects with healthy eyes, ocular hypertension and pigment dispersion syndrome - Huchzermeyer, Cord; Reulbach, Udo; Horn, Folkert; Lämmer, Robert; Mardin, Christian Y.; Jünemann, Anselm (Bmc Ophthalmology, 2014)
The diurnal fluctuation of intraocular pressure may be relevant in glaucoma. The aim of this study was to find out whether the timing of diurnal fluctuation is stable over the years.Long-term IOP data from the Erlangen Glaucoma Registry, consisting of several annual extended diurnal IOP profiles for each patient, was retrospectively analyzed. Normal subjects, patients with ocular hypertension and with pigment dispersion syndrome were included because these subjects had not been treated with antiglaucomatous medications at the time of data acquisition. A cosine curve was fitted to the IOP data and the stability of individual rhythms over the years was tested using the Rayleigh test. To compare the peak times among groups, means were calculated only from subjects with a significant Rayleigh test.Of the fifty-two eligible subjects, a total of 364 extended diurnal IOP profiles measured in a sitting position had been collected over a period of 114 ± 39 months. The Rayleigh test indicated intraindividual stability of phase timing only in 19 subjects (36%). In subjects with pigment dispersions syndrome, peak IOP occurred on average two hours and seven minutes later during the day compared with subjects without this condition (p = 0.05).Fitting of cosine curves to the clinical IOP profiles was generally feasible, although careful interpretation is warranted due to lack of measurements in supine position and between midnight and 7 am. The interesting observation of a phase lag in eyes with pigment dispersion syndrome warrants confirmation and exploration in future prospective studies. The analysis of the IOP data showed no stable individual rhythm in the long term in a majority of patients.
EVALuna2:21175

Long Term Follow-Up of Preperimetric Open-Angle Glaucoma: Improvement of the Visual Field in Morphological Stable Patients Only - Jünemann, Anselm; Bellios, N.; Lämmer, Robert; Link, B.; Mardin, C. Y.; Kremers, Jan; Kruse, Friedrich; Horn, Folkert (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields

MIGS – eine Off-label-Option für eine therapierefraktäre, steroidinduzierte okuläre Hypertension - Hohberger, Bettina; Haug, Marius; Bergua, Antonio; Lämmer, Robert (Ophthalmologe, 2019)
Steroid-induced ocular hypertension (SIOH), which cannot be regulated by topical antiglaucoma agents, is a rare complication after intravitreal implantation of diverse cortisone derivatives. This case report presents a therapeutic approach for treatment-refractory SIOH after intravitreal implantation of fluocinolone acetonide using various minimally invasive glaucoma surgery (MIGS) techniques.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Glaucoma; iStent inject; MIGS; Ocular hypertension; Xen gel stent

MIGS: therapeutic success of combined Xen Gel Stent implantation with cataract surgery - Hohberger, Bettina; Welge-Luessen, Ulrich-Christoph; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: Glaucoma, a common disease in the elderly population, is frequently coexistent with cataract. While the combination of filtration surgery and cataract surgery is a challenging topic with limited success, minimal invasive glaucoma surgery (MIGS), such as Xen Gel Stents, seems to provide promising results. The aim of this study was to investigate the complete and qualified therapeutic success of Xen Gel Stent implantation with (XenPhaco) and without cataract surgery. METHODS: One hundred and eleven open-angle glaucoma eyes underwent implantation of Xen45 Gel Stent (AqueSys, Inc.) with or without cataract operation. Complete therapeutic success was defined as target intraocular pressure (IOP) < 18 mmHg at any time point within 6 months of follow-up without local antiglaucomatous therapy or further surgical interventions. Qualified success was defined as target IOP <18 mmHg with additional 1-2 local antiglaucomatous eye drops. Failure included all cases with the necessity of at least three local antiglaucomatous eye drops or additional glaucoma surgery. RESULTS: Combined implantation of Xen Gel Stent with cataract surgery was performed in 30 eyes and stand-alone Xen Gel Stent implantation was performed in 81 eyes. A complete therapeutic success was achieved in 46.9% of single Xen Gel Stent implantation, whereas 53.3% was reached with combined XenPhaco. Qualified success was seen in 2.5% in the eyes of the single Xen Gel Stent implantation group and in 3.3% of the combined surgery group. Therapeutic failure rate was 49.4% in the stand-alone group vs 46.7% in the combined group. Data were not significantly different for group and subgroup analyses. CONCLUSIONS: Complete and qualified therapeutic success is similar for the combination of Xen Gel Stent implantation with and without cataract surgery in open-angle glaucoma patients. MIGS using Xen Gel Stent can be recommended in situations if glaucoma surgery is indicated besides coexisting cataract.
EVALuna2:34754

OCT-Angiography: agonistic beta 2-adrenergic receptor autoantibodies and FAZ-to-FAZ-ratio in glaucoma patients - Mardin, Christian Y.; Hosari, Sami; Wallukat, Gerd; Kunze, Rudolf; Herrmann, Martin; Lämmer, Robert; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

On- and off-response ERGs elicited by sawtooth stimuli in normal subjects and glaucoma patients - Pangeni, Gobinda; Lämmer, Robert; Tornow, Ralf-Peter; Horn, Folkert; Kremers, Jan (Documenta Ophthalmologica, 2012)
The aim of this study is to measure the on- and off-responses and their response asymmetries elicited by sawtooth stimuli in normal subjects and glaucoma patients. Furthermore, the correlation between the ERGs and other functional and structural parameters are investigated. Full-field stimuli were produced using a Ganzfeld bowl with Light Emitting Diodes (LEDs) as light sources. On- and off-response ERGs were recorded from 17 healthy subjects, 12 pre-perimetric and 15 perimetric glaucoma patients using 4-Hz luminance rapid-on and rapid-off sawtooth stimuli (white light; mean luminance 55 cd/m(2)) at 100% contrast. The on- and off-responses were added to study response asymmetries. In addition, flash ERGs were elicited by red stimuli (200 cd/m(2)) on a blue background (10 cd/m(2)). The mean deviations (MD) of the visual field defects were obtained by standard automated perimetry. The retinal nerve fibre layer thickness (RNFLT) was measured with Spectral Domain Optical Coherence Tomography (SOCT). We studied the correlation between ERG response amplitudes, visual field mean deviation (MDs) and RNFLT values. The on-responses showed an initial negative (N-on) followed by a positive (P-on), a late positive (LP-on) and a late negative responses (LN-on). The off-responses showed an initial positive (P-off) a late positive (LP-off) and a late negative response (LN-off). The addition of on- and off-responses revealed an initial positive (P-add) and a late negative response (LN-add). The on-response components (N-on, P-on and LN-on) in the glaucoma patients were relatively similar to those of the control subjects. However, the LP-on was significantly elevated (p = 0.03) in perimetric patients. The LP-off was significantly elevated (p < 0.001), and the amplitude of LN-off was significantly reduced in perimetric patients (p = 0.02). The LN-add amplitude was significantly reduced (p < 0.001) and delayed (p = 0.03) in perimetric patients. The amplitudes of the LN-off and LN-add ERG components were significantly correlated with the PhNR in the flash ERG (LN-off: p = 0.01; LN-add: p < 0.001) and with RNFLT (LN-off: p = 0.006; LN-add: p = 0.001). On- and off-response ERGs and their response asymmetries, elicited by sawtooth stimuli, are altered in the glaucoma patients. The late components are affected. Changes in the late negative components are correlated with structural and other functional changes.
EVALuna2:21076
Keywords: Electroretinogram; On- and off-responses; Glaucoma; Sawtooth stimuli

Optical coherence tomography in patients with a history of juvenile multiple sclerosis reveals early retinal damage - Huhn, K.; Lämmer, Robert; Oberwahrenbrock, T.; Laemmer, A.; Waschbisch, Anne; Gosar, D.; Brandt, A.; Paul, Friedemann; Linker, R. A.; Lee, D. -H. (European Journal of Neurology, 2015)
Some 3%-10% of patients with multiple sclerosis (MS) experience disease onset before the age of 18 years ('early' onset MS, EOMS). Optical coherence tomography is a non-invasive method to measure retinal nerve fibre layer thickness (RNFLT) and total macular volume (TMV) and may be useful to differentiate axonal and neuronal damage in the retina of patients with a history of EOMS. Here RNFLT and TMV in EOMS patients after a mean disease duration of 11.6 years were compared with patients with age- or disease-duration-matched later onset MS (LOMS) and healthy controls (HCs).In this observational cross-sectional study at two German academic MS centres, RNFLT and TMV were measured by spectral-domain optical coherence tomography in 32 HCs, 36 EOMS (mean age at onset 15.5 ± 2.0 years) and 58 LOMS patients.In comparison with HCs, EOMS patients displayed a significant reduction of RNFLT and TMV independently of a history of optic neuritis. In particular, RNFLT loss in EOMS was similar to that in LOMS and TMV loss was slightly higher compared with disease-duration-matched LOMS. In a generalized estimating model, the EOMS group also displayed a similar correlation between disease duration and RNFLT or TMV loss to LOMS patients.These data argue for a significant amount of axonal and neuronal damage in the retina of EOMS patients and may provide a structural basis for the observation that EOMS patients reach states of irreversible disability at a younger age than patients with LOMS.
EVALuna2:21183

Pattern electroretinogram, blue-yellow visual evoked potentials and the risk of developing visual field defects in glaucoma suspects: a longitudinal “survival” analysis with a very long follow-up - Huchzermeyer, Cord; Lämmer, Robert; Mardin, Christian Y.; Kruse, Friedrich; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2024)
Purpose: Estimating glaucoma suspects’ risk for visual field defects helps to avoid under- and over-treatment. In this retrospective, longitudinal cohort study with a very long follow-up, we studied whether pattern electroretinograms (PERG) amplitudes and blue-on-yellow visual evoked potential (BY-VEP) latencies can predict visual field defects. Methods: Participants of the Erlangen Glaucoma Study were examined with PERG and BY-VEP between 9/1991 and 8/2001. Stimuli were created using an optical bench with Maxwellian view and consisted of vertical gratings (0,88 cpd) in a 32° field for both PERG and BY-VEP. Patients were treated according to clinical standards and performed standard automated perimetry (SAP) annually. Retrospectively, patients with normal SAP at baseline were selected. Primary endpoint was conversion to perimetric glaucoma. Predictive value was modeled using Kaplan–Meier analyses and a multivariate cox proportional hazards model with the continuous variables PERG amplitude, BY-VEP peak time and SAP square-root of loss variance (sLV) after stratification for Jonas classification of the optic discs. Results: Of 412 patients (288: Jonas 0, 103: I, and 21: II; baseline age: 20–60 years), 65 converted to perimetric glaucoma during follow-up (0.5–23.3 years; median 5.5 years). Optic disc classification was a strong risk factor for conversion (log rank p < 0.0001), and patients with more advanced changes progressed earlier. In the multivariate analysis (log rank p = 0.005), only PERG amplitude remained an independent risk factor after stratification for optic disc morphology (p = 0.021), with a 30% higher risk per μV amplitude decrease. Conclusions: PERG helps to estimate glaucoma suspects’ risk for visual field defects.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Electroretinogram; Glaucoma; Perimetry; Survival analysis; Visually evoked potentials

Perimetric measurements with flicker-defined form stimulation in comparison with conventional perimetry and retinal nerve fiber measurements - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
We compared the results of flicker-defined form (FDF) perimetry with standard automated perimetry (SAP) and retinal nerve fiber layer (RNFL) thickness measurements using spectral domain optical coherence tomography (OCT).A total of 64 healthy subjects, 45 ocular hypertensive patients, and 97 "early" open-angle glaucoma (OAG) patients participated in this study. Definition of glaucoma was based exclusively on glaucomatous optic disc appearance. All subjects underwent FDF perimetry, SAP, and peripapillary measurements of the RNFL thickness. The FDF perimetry and SAP were performed at identical test locations (G1 protocol). Exclusion criteria were subjects younger than 34 years, SAP mean defect (SAP MD) > 5 dB, eye diseases other than glaucoma, or nonreliable FDF measurements. The correlations between the perimetric data on one hand and RNFL thicknesses on the other hand were analyzed statistically.The age-corrected sensitivity values and the local results from the controls were used to determine FDF mean defect (FDF MD). The FDF perimetry and SAP showed high concordance in this cohort of experienced patients (MD values, R = -0.69, P < 0.001). Of a total of 42 OAG patients with abnormal SAP MD, 38 also displayed abnormal FDF MD. However, FDF MD was abnormal in 28 of 55 OAG patients with normal SAP MD. The FDF MD was significantly (R = -0.61, P < 0.001) correlated with RNFL thickness with a (nonsignificantly) larger correlation coefficient than conventional SAP MD (R = -0.48, P < 0.001).The FDF perimetry is able to uncover functional changes concurrent with the changes in RNFL thickness. The FDF perimetry may be an efficient functional test to detect early glaucomatous nerve atrophy. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21150

Perimetrie in der Glaukomdiagnostik - Lämmer, Robert; Huchzermeyer, Cord (Klinische Monatsblätter für Augenheilkunde, 2021)
CRIS-Team Scopus Importer:2021-03-05
Keywords: early detection; frequency doubling perimetry; glaucoma; visual field

Perimetry in the Diagnosis of Glaucoma - Lämmer, Robert; Huchzermeyer, Cord (Augenheilkunde up2date, 2021)
CRIS-Team WoS Importer:2021-03-12

Pigment dispersion syndrome and pigmentary glaucoma. Morphometric analysis of the anterior chamber segment with SL-OCT - Birner, Barbara; Tourtas, T.; Wessel, J. M.; Jünemann, Anselm; Mardin, Christian Y.; Kruse, Friedrich; Lämmer, Robert (Ophthalmologe, 2014)
The purpose of this study was to analyze if anterior chamber parameters are risk factors for the development of pigment dispersion syndrome (PDS) and/or for the conversion to pigmentary glaucoma (PG).This study included a total of 63 eyes from 35 patients with PDS and PG and 65 eyes from 49 unaffected volunteers as the control group. The following parameters were measured by slit lamp optical coherence tomography (SL-OCT): anterior chamber volume (ACV) and depth (ACD), angle opening distance (AOD) and the trabecular iris space area (TISA) at 500 µm and 750 ?m from the scleral spur. Comparisons between the following groups were performed: between the PDS/PG and the control group, between PDS and PG and between male and female patients.The results of ACV, ACD, AOD and TISA were significantly higher in PDS/PG patients when compared to the control group. There were no significant differences between PDS and PG. The gender-specific comparison also showed no significant differences.Significantly higher anterior chamber parameters are a possible risk factor for development of PDS; however, a higher risk of conversion to PG does not seem to correlate with increased anterior chamber parameters. The parameters of the anterior chamber are apparently not associated with the male predominance of PDS and PG.
EVALuna2:21131

Possible Impact of functional active GPCR-autoantibodies on retinal microcirculation in Long-COVID - Mardin, Christian Y.; Lucio, Marianna; Wallukat, Gerd; Szewczykowski, Charlotte; Hoffmanns, Jacob; Raith, Franziska; Schröder, Tim; Schottenhamml, Julia; Lämmer, Robert; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Post-COVID-19 Syndrome: Retinal Microcirculation as a Potential Marker for Chronic Fatigue - Schlick, Sarah; Lucio, Marianna; Wallukat, Gerd; Bartsch, Alexander; Skornia, Adam; Hoffmanns, Jakob; Szewczykowski, Charlotte; Schröder, Thora; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; et al. (International Journal of Molecular Sciences, 2022)
Post-COVID-19 syndrome (PCS) is characterized by persisting sequelae after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). PCS can affect patients with all COVID-19 disease severities. As previous studies have revealed impaired blood flow as a provoking factor triggering PCS, it was the aim of the present study to investigate the potential association between self-reported chronic fatigue and retinal microcirculation in patients with PCS, potentially indicating an objective biomarker. A prospective study was performed, including 201 subjects: 173 patients with PCS and 28 controls. Retinal microcirculation was visualized by OCT angiography (OCT-A) and quantified using the Erlangen-Angio-Tool as macula and peripapillary vessel density (VD). Chronic fatigue (CF) was assessed according to the variables of Bell’s score, age and gender. VDs in the superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP) were analyzed, considering the repetitions (12 times). Seropositivity for autoantibodies targeting G protein-coupled receptors (GPCR-AAbs) was determined by an established cardiomyocyte bioassay. Taking account of the repetitions, a mixed model was performed to detect possible differences in the least square means between the different groups included in the analysis. An age effect in relation to VD was observed between patients and controls (p < 0.0001). Gender analysis showed that women with PCS showed lower VD levels in the SVP compared to male patients (p = 0.0015). The PCS patients showed significantly lower VDs in the ICP as compared to the controls (p = 0.0001 (CI: 0.32; 1)). Moreover, considering PCS patients, the mixed model revealed a significant difference between those with chronic fatigue (CF) and those without CF with respect to VDs in the SVP (p = 0.0033 (CI: −4.5; −0.92)). The model included variables of age, gender and Bell’s score, representing a subjective marker for CF. Consequently, retinal microcirculation might serve as an objective biomarker in subjectively reported chronic fatigue in patients with PCS.
CRIS-Team Scopus Importer:2022-12-09
Keywords: chronic fatigue; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; long COVID syndrome; OCT angiography; post-COVID-19 syndrome; retinal microcirculation

Precision of Optic Nerve Head and Retinal Nerve Fiber Layer Parameter Measurements by Spectral-domain Optical Coherence Tomography - Schrems-Hösl, Laura-Maria; Schrems, Wolfgang; Lämmer, Robert; Kruse, Friedrich; Mardin, Christian Y. (Journal of Glaucoma, 2018)
PURPOSE: The aim of this study was to assess the repeatability and reproducibility (R&R) of Bruch membrane opening based on minimum rim width (BMO-MRW), minimum rim area (BMO-MRA) and peripapillary retinal nerve fiber layer thickness (RNFLT) with the Spectralis optical coherence tomography (Heidelberg Engineering) for normal and glaucoma subjects. Precise measurement of these parameters can support detection of structural glaucomatous damage and progression. METHODS: This cross-sectional study included 16 healthy controls and 16 patients with glaucoma. One eye was randomly selected and included in this study. Subjects underwent 1 baseline and 3 follow-up measurements, using 3 different Spectralis optical coherence tomography devices in randomized order, each operated by a single operator. Outcome measures were global and sectorial averages of BMO-MRW and BMO-MRA, and of peripapillary RNFLT obtained from 12/14/16-degree circle scans. Coefficients of variation (COV) were calculated and a mixed-effects analysis of variance was performed to compare R&R between devices. RESULTS: COVs of global and sectorial BMO-MRW measurement under repeatability conditions ranged from 0.51% to 1.7% (normal, 0.62% to 1.3%; glaucoma, 0.64% to 2.3%). Respective COVs under reproducibility conditions ranged from 0.89% to 1.9% (normal, 0.77% to 2.8%; glaucoma, 1.1% to 2.6%). COVs of global and sectorial RNFLT measurements under repeatability conditions ranged from 0.5% to 2.8%. Respective COVs under reproducibility conditions ranged from 1.6% to 3.5%. CONCLUSIONS: For R&R, the COVs of measured parameters were by trend higher for glaucoma eyes compared with normal controls. The BMO-MRW measurement system has an excellent precision taking into account that major and minor corrections of segmentation have to be done by the examiner before evaluation.
EVALuna2:34751

Predicted and Measured Retinal Nerve Fiber Layer Thickness From Time-Domain Optical Coherence Tomography Compared With Spectral-Domain Optical Coherence Tomography - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Bendschneider, Delia; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Horn, Folkert (JAMA Ophthalmology, 2015)
New methods are needed to compare peripapillary retinal nerve fiber layer thickness (pRNFLT) measurements taken from time-domain optical coherence tomography (TD-OCT) and spectral-domain OCT (SD-OCT).To compare the agreement of measured and predicted pRNFLT using different equations based on pRNFLT measurements obtained by TD-OCT and SD-OCT.Cross-sectional single-center study that took place at the Department of Ophthalmology, University of Erlangen-Nuremberg from November 16, 2005, to June 3, 2015, and included 138 eyes of control participants, 126 eyes of patients with ocular hypertension, 128 eyes of patients with preperimetric glaucoma, and 160 eyes of patients with perimetric glaucoma. All participants had standard clinical examinations to obtain TD-OCT (via Stratus OCT) and SD-OCT (via Spectralis OCT) measurements of pRNFLT. Two groups were matched for diagnostic subgroup, eye side, sex, and age. The TD-OCT measurements of the first group were used to predict the mean SD-OCT and 6-sector vertical-split pRNFLT measurements of the second group and vice versa. The agreement between the predicted pRNFLT calculations of conversion equations and measured pRNFLT of the second group was evaluated by intraclass correlation coefficients and Bland-Altman plots.Mean and sectoral pRNFLT measurements obtained by TD-OCT and SD-OCT as well as the agreement between measured and predicted pRNFLT.The agreement for all investigated equations to predict mean pRNFLT measurements with intraclass correlation coeffecients ranged from 0.937 to 0.939. Bland-Altman plots demonstrated systemic biases between -0.7 ?m and +1.1 ?m for measured and predicted mean pRNFLT measurements. The ratio method demonstrated an intraclass correlation coefficient of 0.969 for the temporal-inferior sector. The best color-code agreement between both OCT devices was achieved by the no conversion method, with ? = 0.731 (95% CI, 0.656-0.806) for the mean pRNFLT.These data suggest that the prediction of mean pRNFLT values by equations derived from TD-OCT and SD-OCT can be conducted with high levels of agreement. In individual cases and singular sectors, high prediction errors may occur. When longitudinal imaging data from both TD-OCT and SD-OCT are available, conversion equations may provide longitudinal comparability.
EVALuna2:21226

Predictive Factors for Visual Field Conversion: Comparison of Scanning Laser Polarimetry and Optical Coherence Tomography - Diekmann, Theresa; Schrems-Hösl, Laura-Maria; Mardin, Christian Y.; Lämmer, Robert; Horn, Folkert; Kruse, Friedrich; Schrems, Wolfgang (Journal of Glaucoma, 2018)
PURPOSE: The purpose of this study was to compare the ability of scanning laser polarimetry (SLP) and spectral-domain optical coherence tomography (SD-OCT) to predict future visual field conversion of subjects with ocular hypertension and early glaucoma. METHODS: All patients were recruited from the Erlangen glaucoma registry and examined using standard automated perimetry, 24-hour intraocular pressure profile, and optic disc photography. Peripapillary retinal nerve fiber layer thickness (RNFL) measurements were obtained by SLP (GDx-VCC) and SD-OCT (Spectralis OCT). Positive and negative predictive values (PPV, NPV) were calculated for morphologic parameters of SLP and SD-OCT. Kaplan-Meier survival curves were plotted and log-rank tests were performed to compare the survival distributions. Contingency tables and Venn-diagrams were calculated to compare the predictive ability. RESULTS: The study included 207 patients-75 with ocular hypertension, 85 with early glaucoma, and 47 controls. Median follow-up was 4.5 years. A total of 29 patients (14.0%) developed visual field conversion during follow-up. SLP temporal-inferior RNFL [0.667; 95% confidence interval (CI), 0.281-0.935] and SD-OCT temporal-inferior RNFL (0.571; 95% CI, 0.317-0.802) achieved the highest PPV; nerve fiber indicator (0.923; 95% CI, 0.876-0.957) and SD-OCT mean (0.898; 95% CI, 0.847-0.937) achieved the highest NPV of all investigated parameters. The Kaplan-Meier curves confirmed significantly higher survival for subjects within normal limits of measurements of both devices (P<0.001). Venn diagrams tested with McNemar test statistics showed no significant difference for PPV (P=0.219) or NPV (P=0.678). CONCLUSIONS: Both GDx-VCC and SD-OCT demonstrate comparable results in predicting future visual field conversion if taking typical scans for GDx-VCC. In addition, the likelihood ratios suggest that GDx-VCC's nerve fiber indicator<30 may be the most useful parameter to confirm future nonconversion. (http://www.ClinicalTrials.gov number, NTC00494923; Erlangen Glaucoma Registry).
EVALuna2:34215

Responses of postreceptoral pathways elicited by L- And M-cone isolating ON- And OFF-electroretinograms in glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. To compare the electroretinographical (ERG) responses elicited by L- and M-cone isolating ON- and OFF-sawtooth stimuli in normal subjects and glaucoma patients. METHODS. Twenty-one normal subjects and 44 primary open-angle glaucoma patients participated in the study. L- and M-cone isolating (18% cone contrast; 284 cd/m2) rapid ON- and rapid OFF-sawtooth (4 Hz) stimuli with two stimulus sizes (full-field (FF) and central 70° diameter) were generated using the triple silent substitution technique. ON- and OFF-response asymmetries were studied by adding the two (to obtain L-add and M-add responses). The initial positive (P) and subsequent late negative (LN) components of the L-add and M-add ERGs were compared between the subject groups and correlated with retinal nerve fiber layer thickness (RNFLT) and pattern ERG responses. RESULTS. The responses to L-ON and to M-OFF stimuli and vice versa resembled each other particularly with 70° stimuli. The PL-add amplitudes were not significantly different between the normal subjects and glaucoma patients, whereas the LNL-add amplitude was significantly (P < 0.01) smaller in the glaucoma patients. Both PM-add and LNM-add were not significantly different between the subject groups. The PERG amplitude with 0.8° check sizes and the 0.8°/16° amplitude ratio (PERG ratio) were significantly (P < 0.05) different between the subject groups. The 70° LNL-add amplitude and the 0.8° PERG amplitude were significantly correlated with RNFLT. CONCLUSIONS. The ERGs to 70° cone isolating sawtooth stimuli reflect cone opponency. The cone opponent ERG responses were not significantly different between glaucoma patients and normal subjects. Luminance driven L-add responses were significantly different, indicating that central luminance signals are mainly affected in glaucoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Glaucoma; Magnocellular; ON- and OFF electroretinogram; Parvocellular; Sawtooth stimuli; Silent substitution; Stimulus size

Retinal imaging and axonal degeneration in later onset multiple sclerosis - Huhn, Konstantin; Lämmer, Robert; Meng, Hanna Zimmermann; Laemmer, Alexandra; Waschbisch, Anne; Utz, Kathrin; Giess, Rene Markus; Paul, Friedemann; Linker, Ralf; Lee, De-Hyung (Journal of the Neurological Sciences, 2016)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the CNS typically affecting younger adults and resulting in neuro-axonal degeneration already at early stages of the disease. Less is known about the effects of a later disease onset (LOMS, onset >50years of age). Analysis of retinal layers by optical coherence tomography (OCT) is a non-invasive method to investigate retinal and neuro-axonal degeneration. We applied OCT to detect differences in retinal damage depending on a later disease manifestation.14 LOMS patients, 14 age- and 14 disease duration-matched normal onset (NOMS) patients with a relapsing remitting disease course and 15 healthy controls (HC) were included. OCT measurement of peripapillary retinal nerve fiber layer (RNFL), total macular volume (TMV), combined ganglion cell/inner plexiform layer (GCIPL), inner nuclear layer (INL) and outer retinal layers (ORL) was conducted. Furthermore, analysis of clinical features and of effects of previous optic neuritis (ON) was performed RESULTS: In a GEE based analysis of age- and disease duration matched NOMS, LOMS patients show no significant differences in retinal layer thickness whereas ON significantly reduced thickness of retinal layers. All MS groups display lower retinal layer thickness as compared to HC independently of type of onset.Our LOMS findings are well in line with published OCT data of normal onset MS. As the degree of retinal layer thinning was similar in MS subgroups, retinal neurodegeneration in MS may occur independently of time of disease onset.
EVALuna2:21282

Risk factors for ocular hypotony after XEN Gel Stent implantation - Galimi, Maria E.; Weller, Julia; Kruse, Friedrich; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: To investigate the incidence of postoperative hypotony, and risk factors for the development of hypotony in eyes who had undergone XEN Gel Stent implantation. Methods: In this retrospective, single-centre case series, medical records of 170 consecutive eyes who had undergone XEN Gel Stent implantation with or without simultaneous phacoemulsification for primary or secondary open angle glaucoma were analysed. Primary outcome parameters were the incidence of postoperative hypotony and potential risk factors for its development, and secondary parameters were pre- and postoperative visual acuity, intraocular pressure (IOP), and number of IOP-lowering eye drops. Results: Postoperative hypotony ≤ 6 mmHg occurred in 57% of eyes. Hypotony was without complications in 70.1%, 13.4% had transient complications with spontaneous resolution, and 16.5% had complications requiring treatment. Mean visual acuity logMAR before surgery accounted for 0.47 ± 0.46 in all eyes and 0.47 ± 0.48 at the 4-week visit. There was no significant difference of BCVA in the group of eyes with and without postoperative hypotony before and after surgery. The mean IOP before surgery was 24.6 ± 8.4 mmHg and decreased significantly to 18.4 ± 10.2 after 4 weeks. Eyes with an axial length over 24.3 mm had a threefold increased risk for postoperative hypotony (OR 3.226, 95% confidence interval 1.121–9.279). This risk was decreased in eyes with simultaneous cataract surgery (OR 0.483, 95% confidence interval 0.258–0.903). Conclusion: In our sample, postoperative hypotony was a common complication after XEN Gel Stent implantation, but serious, persistent complications were rare. A longer axial length predisposes the eye for the development of hypotony.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-10-21
Keywords: Glaucoma; Hypotony; Minimal invasive glaucoma surgery (MIGS); XEN Gel Stent

Serum Selenium Levels in Glaucoma: A Pilot Study - Lucio, Marianna; Fick, Alexander; Michalke, Bernhard; Lämmer, Robert; Hosari, Sami; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Trace elements are assumed to be involved in glaucoma pathogenesis via changes in oxidative stress. Especially serum selenium (Se) has been linked to this neurodegenerative disease. Serum Se levels differ between countries due to nutrition and ethnicity. It was the aim of the present study to investigate serum Se levels in primary open-angle glaucoma (POAG) patients and controls in Germany and to consider potential age and gender effects. Material and Methods The Se concentration of 39 serum samples (22 patients with POAG, 17 controls) were analyzed by inductively coupled plasma-sector field mass spectrometry (ICP-sf-MS) in high resolution mode. Covariance and percentile regression were analyzed. Age and gender were defined as confounding factors and their different trends were investigated. Moreover, age was examined across different quantiles of Se levels. Results Total serum least-squares means (LS-means) Se levels were 132.02 μg/L (controls) and 134.86 μg/L (POAG). Total serum Se levels did not differ between the study groups (p > 0.05). Significant age and gender effects of serum Se were observed. Quantile analysis showed that the 1st serum Se quantile decreased with increasing age in POAG patients in contrast to controls. The odds ratios of the 1st serum Se were 1.3 (with 2nd quantile) and 1.3 (with 3rd quantile), respectively. Conclusion The serum Se level of the German cohort was almost half of those of the published US cohort (glaucoma 209.11 ng/mL; control 194.45 ng/mL). Age and gender effects were observed; the serum Se level increased with age in women (controls and POAG), however, Se levels decreased with age in men (controls and POAG).
CRIS-Team Scopus Importer:2021-03-05
Keywords: age; gender; glaucoma; ICP-sf-MS; selenium; trace element

Short-term fluctuation of intraocular pressure is higher in patients with pseudoexfoliation syndrome despite similar mean intraocular pressure: a retrospective case-control study - Huchzermeyer, Cord; Horn, Folkert; Lämmer, Robert; Mardin, Christian Y.; Junemann, Anselm G. M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
Higher levels of short-term fluctuation of intraocular pressure (IOP) are characteristic of pseudoexfoliation syndrome (PEX). However, it is not known whether they are just a side effect of the higher mean intraocular pressure (IOP) or an independent feature. The purpose of this study was to compare short-term fluctuation of IOP between eyes with PEX and control eyes that were matched as closely as possible for mean IOP.In this retrospective case-control study, all patients with confirmed PEX were identified from the database of the Erlangen Glaucoma Registry. From the same database, matched control eyes with similar treatment, age, glaucoma stage, and mean IOP were identified. For each patient, data from multiple extended diurnal IOP profiles were available.Seventy-eight eyes were included in the study (39 with PEX and 39 matched control eyes). Although a very close match was achieved, a small but statistically significant difference in mean IOP was still present, but this did not seem to explain the differences in IOP fluctuation levels. Eyes with PEX had significantly higher short-term IOP fluctuations (SD of IOP and range of IOP).The higher levels of short-term fluctuation in IOP appear to be an independent feature of PEX and not merely a secondary effect of the higher mean IOP. We suggest that this may have practical implications, even if IOP fluctuation levels should not prove to be an independent risk factor for development/progression of glaucoma, because more frequent measurements are needed in these patients to obtain good estimates of mean IOP and changes in IOP under treatment.
EVALuna2:21176

Spatial properties of L- and M-cone driven incremental (on-) and decremental (off-) electroretinograms: normal subjects Vs. glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Structural changes of macular inner retinal layers in early normal-tension and high-tension glaucoma by spectral-domain optical coherence tomography - Edlinger, Florian S. M.; Schrems-Hösl, Laura-Maria; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Schrems, Wolfgang (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: Assessment of the diagnostic ability of segmented macular inner retinal layer thickness and peripapillary retinal nerve fiber layer (pRNFL) measured by spectral-domain optical coherence tomography (SD-OCT) in patients with normal-tension (NT) and high-tension (HT) perimetric and preperimetric glaucoma. METHODS: The 212 participants included 45 healthy subjects, 55 patients with ocular hypertension, 56 patients with preperimetric glaucoma, and 56 patients with perimetric glaucoma. The preperimetric and perimetric groups were further subdivided into NT and HT groups. Sectoral and global thickness of macular retinal nerve fiber layer (mRNFL), ganglion cell layer (mGCL), inner plexiform layer (mIPL), ganglion cell complex (mGCC), and pRNFL were measured using SD-OCT (Spectralis, Heidelberg Engineering, Germany). Diagnostic performance was ascertained by sectoral and global comparison of the sensitivities at specificity ≥ 95%. RESULTS: For all layers, the largest thickness decrease was reported in the HT perimetric group. In all groups, the sensitivities of mGCL showed a comparable diagnostic value to pRNFL in order to distinguish between healthy subjects and glaucoma patients. In the perimetric group, mGCL (85.7%) exhibited higher sensitivities than mRNFL (78.6%) and mGCC (78.6%). Both mRNFL and pRNFL demonstrated equal diagnostic performance in the HT perimetric group (88.5 and 96.2%), in the NT groups, mRNFL was inferior to all other layers. CONCLUSION: The sensitivities of mGCL and mRNFL were comparable to the sensitivities of pRNFL. In clinical application, mGCL and mRNFL, with a focus on the temporal and inferior sectors, may provide a convincing supplementation to pRNFL. CLINICAL TRIAL REGISTRATION: Erlangen Glaucoma Registry www.clinicaltrials.gov ID: NCT00494923.
EVALuna2:34747

Summation of Temporal L-Cone- and M-Cone-Contrast in the Magno- and Parvocellular Retino-Geniculate Systems in Glaucoma - Huchzermeyer, Cord; Horn, Folkert; Lämmer, Robert; Mardin, Christian; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
Purpose: The purpose of this study was to characterize summation of temporal L- and M-cone contrasts in the parvo- (P-) and magnocellular (M-) pathways in glaucoma and the relationship between the respective temporal contrast sensitivities (tCS) and clinical parameters. Methods: Perifoveal tCS to isolated or combined L- and M-cone contrasts (with different contrast ratios, and therefore different luminance and chromatic components) were measured at different temporal frequencies (at 1 or 2 Hz and at 20 Hz) using triple silent substitution in 73 subjects (13 healthy, 25 with glaucoma, and 35 with perimetric glaucoma). A vector summation model was used to analyze whether perception was driven by the P-pathway, the M-pathway, or both. Using this model, L- and M-cone input strengths (AL, AM) and phase differences between L- and M-cone inputs were estimated. Results: Perception was always mediated by the P-pathway at low frequencies, as indicated by a median phase angle of 179.84 degrees (cone opponency) and a median AL/AM ratio of 1.04 (balanced L- and M-cone input strengths). In contrast, perception was exclusively mediated by the M-pathway at higher frequencies (input strength not balanced: AL/AM = 2.94, median phase angles = 130.17 degrees). Differences in phase were not significant between diagnosis groups (Kruskal-Wallis = 0.092 for P- and 0.35 for M-pathway). We found differences between groups only for the M-pathway (L-cone tCS deviations at 20 Hz were significantly lower in the patients with glaucoma P = 0.014, with a strong tendency in M-cones P = 0.049). L-cone driven tCS deviations at 20 Hz were linearly correlated with perimetric mean defect (MD) and quadratically correlated with retinal nerve fiber layer (RNFL) thickness. Conclusions: Unaltered phase angles between L- and M-cone inputs in glaucoma indicated intact temporal processing. Only in the M-pathway, contrast sensitivity deviations were closely related to diagnosis group, MD, and RNFL thickness, indicating M-pathway involvement.
CRIS-Team Scopus Importer:2021-06-04

Switch of inhibitory to agonistic autoantibodies directed against the beta 2-adrenergic receptor in the pathogenesis of pseudoexfoliation syndrome and glaucoma - Hohberger, Bettina; Herrmann, Martin; Schlötzer-Schrehardt, Ursula; Mardin, Christian Y.; Lämmer, Robert; Kunze, Rudolf; Wallukat, Gerd (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-17

Temporal Contrast Sensitivities are Locally Reduced around 4Hz for L-cone- and around 10Hz for M-cone isolating stimuli in Glaucoma Patients - Huchzermeyer, Cord; Haubner, Sarah; Lämmer, Robert; Mardin, Christian Y.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

The Effect of Long-term Antiglaucomatous Drug Administration on Central Corneal Thickness - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Mardin, Christian Y.; Horn, Folkert; Jünemann, Anselm; Kruse, Friedrich; Braun, Joachim M.; Lämmer, Robert (Journal of Glaucoma, 2016)
To evaluate rates of changes per year of central corneal thickness after antiglaucomatous drug administration with ?-blockers, prostaglandin analogs, and carbonic anhydrase inhibitors monotherapy and combined topical antiglaucomatous therapy, in a cohort of patients with ocular hypertension, glaucoma suspects, and patients with perimetric glaucoma as compared with normal controls.This retrospective single-center study included 130 eyes as healthy controls, 121 eyes of ocular hypertensive patients, 105 eyes of glaucoma suspects, and 49 eyes of perimetric glaucoma patients. All patients underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, and optical coherence pachymetry (OCP; Heidelberg Engineering). The cohort was divided into 8 groups on the basis of topical antiglaucomatous medication. Linear regression analysis was conducted to analyze the relationship between central corneal thickness and exposure to antiglaucomatous medication during the follow-up.Central corneal thickness did not change during the follow-up for investigated diagnostic subgroups. There was a statistically significant decrease in central corneal thickness for eyes treated with prostaglandin monotherapy (-3.1 ?m/y for left eye), and a combined therapy with prostaglandins, carbonic anhydrase inhibitors, and ?-blockers (-5.8 and -3.8 ?m/y for right and left eye, respectively).We recommend regular measurements before and during therapy with prostaglandin monotherapy and a combined therapy with prostaglandins, carbonic anhydrase inhibitors, and ?-blockers. Follow-up intraocular pressure measurements may be underestimated for eyes treated with the aforementioned treatment regimens if central corneal thickness is not measured on a regular basis.
EVALuna2:21177

The influence of trace elements on the therapeutic success of suprachoroidal draining devices - Wörn, Maximilian; Lämmer, Robert; Lucio, Marianna; Michalke, Bernhard; Rühl, Eva; Hohberger, Bettina (Journal of Trace Elements in Medicine and Biology, 2023)
Purpose: The therapeutic success of minimal invasive glaucoma surgery (MIGS) is challenging due to many factors including fibrotic or occlusive events. Recent clinical data show sudden peaks of intraocular pressure (IOP) in the postoperative care of glaucoma patients after suprachoroidal draining stents. Yet, the reasons for the IOP peaks are speculative. As a link between trace elements and fibrosis had been previously observed in systemic disorders, the present study aimed to investigate the impact of trace elements on the therapeutic success of the suprachoroidal draining stents in patients with open-angle glaucoma (OAG). Material and Methods: An analysis of a prospective single-center study was done: fifty-five eyes of patients with OAG (29 female, 26 male) underwent Cypass Micro-Stent implantation either as a stand-alone procedure or combined with cataract surgery. All patients underwent pre-operatively an ophthalmological examination which included slit lamp biomicroscopy and fundoscopy. IOP was measured by Goldmann applanation tonometry. Functional and morphometric data were assessed by Octopus G1-perimetry, which included measurement of retinal nerve fiber layer thickness (Spectralis OCT). Data of the patients’ follow-ups were recorded during 18 months post-operatively. The therapeutic success of CyPass Micro-Stent was classified as ‘success’ (IOP reduction ≥20% compared to a pre-operative baseline without any medication), ‘qualified success’ (IOP reduction ≥20 % with same or lower additional eye medication), and ‘failure’ (IOP reduction ≤20 % or additional surgical treatment necessary). Aqueous humour was extracted once during surgery for analysis of the level of 14 trace elements: Copper (Cu), Cadmium (Cd), Cobalt (Co), Chromium (Cr), Iron (Fe), Lithium (Li), Magnesium (Mg), Manganese (Mn), Phosphorus (P), Lead (Pb), Titanium (Ti), Uranium (U), Vanadium (V), and Zinc (Zn). Analysis of the trace elements was done using an ELEMENT 2, ICP-sf-MS instrument (Thermo-Fisher Scientific, Bremen, Germany). Analysis of levels of trace elements was done across the patients’ groups of the three subclasses of therapeutic success. Statistical investigations for substantial differences were conducted using the method of least squares to fit general linear models and mixed models. The last one for the repeated measurements of IOP. Results: Levels of Mg were significantly lower one month postoperatively in the success group (LS-Mean 1.30 mg/L) compared to the qualified success group (LS-Mean 1.22 mg/L; p-value = 0.04). Fe was significantly increased in the failure group (LS-Mean 2.07 µg/L) compared to the qualified success group (LS-Mean 1.64 µg/L; p-value = 0.019) after 3 months of follow-up. Additionally, Fe levels were significantly lower in the success group (LS-Mean 1.47 µg/L) compared to the failure cohort (LS-Mean 2.07 µg/L; p-value = 0.009). After a period of 18 months, significantly higher levels of Mn were observed in the success group (LS-Mean 1.24 µg/L) than in the failure group (LS Mean 0.30 µg/L, p-value = 0.019). Conclusion: The present data might suggest that trace elements can influence therapeutic success of suprachoroidal draining devices postoperatively and thus offer first hints for potential novel therapeutic options.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Fibrosis; Glaucoma; Suprachoroidal draining stents; Surgery; Trace elements

Thickness related textural properties of retinal nerve fiber layer in color fundus images - Odstrcilik, Jan; Kolar, Radim; Tornow, Ralf-Peter; Jan, Jiri; Budai, Attila; Mayer, Markus Anton; Vodakova, Martina; Lämmer, Robert; Lamos, Martin; Kuna, Zdenek; Gazarek, Jiri; Kubena, Tomas; et al. (Computerized Medical Imaging and Graphics, 2014)
Images of ocular fundus are routinely utilized in ophthalmology. Since an examination using fundus camera is relatively fast and cheap procedure, it can be used as a proper diagnostic tool for screening of retinal diseases such as the glaucoma. One of the glaucoma symptoms is progressive atrophy of the retinal nerve fiber layer (RNFL) resulting in variations of the RNFL thickness. Here, we introduce a novel approach to capture these variations using computer-aided analysis of the RNFL textural appearance in standard and easily available color fundus images. The proposed method uses the features based on Gaussian Markov random fields and local binary patterns, together with various regression models for prediction of the RNFL thickness. The approach allows description of the changes in RNFL texture, directly reflecting variations in the RNFL thickness. Evaluation of the method is carried out on 16 normal ("healthy") and 8 glaucomatous eyes. We achieved significant correlation (normals: ?=0.72±0.14; p<<0.05, glaucomatous: ?=0.58±0.10; p<<0.05) between values of the model predicted output and the RNFL thickness measured by optical coherence tomography, which is currently regarded as a standard glaucoma assessment device. The evaluation thus revealed good applicability of the proposed approach to measure possible RNFL thinning.
EVALuna2:21169

Ultrastructural analysis of explanted CyPass microstents and correlation with clinical findings - Hübner, Lisa; Schlötzer-Schrehardt, Ursula; Weller, Julia; Hohberger, Bettina; Mardin, Christian; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: The purpose of this study was to obtain insight into cellular processes after CyPass microstent implantation into the supraciliary space. With this knowledge, we expected to find some reason for surgical failure. Methods: Nine CyPass microstents of 8 patients with primary open-angle glaucoma (n = 1), pseudoexfoliation glaucoma (n = 5), uveitic glaucoma (n = 1), and posttraumatic open-angle glaucoma (n = 1) were explanted due to recurrence of IOP elevation, corneal decompensation, or persistent hypotony. The explants were processed for light and transmission electron microscopy. Results: Fibrotic material, consisting of collagen fibrils, microfibrils, pseudoexfoliation fibrils produced by activated fibroblasts, was detected in the stent lumen of 4/5 pseudoexfoliation glaucoma patients and also in posttraumatic open-angle glaucoma. Fibrotic material was also present on the outer surface and within fenestrations of the majority of stents. Complete absence of fibrotic reaction was noticed in 3 of 9 microstents. Conclusion: Although MIGS is known to be less invasive than conventional surgery, implants placed in the suprachoroidal space may be adversely affected by a fibrotic tissue reaction resulting in implant failure. Understanding mechanisms and risk factors leading to fibrotic scarring following antiglaucomatous surgery may help to develop novel strategies that improve surgical outcome.
CRIS-Team Scopus Importer:2022-03-18
Keywords: CyPass microstent; Fibrosis; Glaucoma; MIGS; Surgery failure

Visual Field Progression Rates in Glaucoma Eyes With Progressive Optic Disc Change - Bellios, N.; Horn, Folkert; Lämmer, Robert; Link, B.; Kremers, Jan; Mardin, C. Y.; Junemann, A. G. (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields